Challenges for humanization in the work of Nursing educators - Magda Ribeiro de Castro; Kayo Henrique Jardel Feitosa Sousa; Flaviana Pereira Bastos Nascimento; Gisele Massante Peixoto Tracera; Katerine Moraes dos Santos; Regina Célia Gollner Zeitoune (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objective: To discuss the challenges for humanization at work, from the perception of Nursing educators. Method: A descriptive, exploratory, and qualitative research study conducted at a public university in Espírito Santo, with 19 Nursing educators who answered the semi-structured interview. Thematic analysis was used for data treatment, constituting two categories: interpersonal relationships and work organization. Results: The challenges for humanization at work were based on relational issues and work overload. Regarding interpersonal relationships, lack of respect and dialog and relationship problems were highlighted. Regarding the organization of work, it encompassed issues related to the content of tasks, workload, excess of activities, and work pressures. Conclusion: Relational elements and work organization are challenges for humanization, affecting the health of the educators and interfering in the organization of healthy and welcoming workspaces, contrary the National Humanization Policy.